Influence of NaCl concentration on pitting corrosion of extruded Al-Mg-Si alloy AA6060 - Jadranka Malina; Jagoda Radošević (Zaštita Materijala)
Extruded Al-Mg-Si alloys (AA6xxx series alloys) are the most common aluminum alloys for structural application due to reliable mechanical characteristics and corrosion properties. Spontaneously formed adherent aluminum oxide film on the surface protects Al and Al -alloys from corrosive attack in neutral media, but in chloride containing solutions, such thin and compact passive film is prone to breakdown. In this study the corrosion behavior of commercial extruded Al-Mg-Si alloy AA6060 was investigated in NaCl solutions of different concentrations using anodic potentiodynamic polarization measurements under deaerated conditions at room temperature. It was shown that sensitivity to chloride attack increase with increasing Cl- concentration and depends on cathodic micro constituents in extruded Al-Mg-Si alloy.